(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
On the same piece of land that once housed the grand first and second Madiston Square Gardens, on Madison Avenue between 26th and 27th streets, rose the New York Life Building. Famed architect Cass Gilbert an early proponent of skyscrapers, was awarded the commission to design the building.